Modern technology and the possibility of their use for the development of the domestic copper industry (Al-Academy, 2016)
Industries copper a craft that requires precision and patience great in the processes of industrialization and execution of product launches brass designs and a variety of forms , and the goal of research into the possibility of the use of modern technologies in the development of industries copper local , and identifies research study models of industries copper local to the city of Baghdad , and are available in the markets for the period from (200 - 2011) , Chapter II Multi industries copper local and technical in the copper industry , and after analysis models the sample was the most important conclusions : can work forms a multi- product copper formations deep or window using the technique work motifs and patterns. - formations decorative ongoing and inscriptions repeated board products copper can be obtained using the technique of metal casting molds